Stres Akademik pada Mahasiswa : Apakah Peranan Problem Focused Coping? - Sholihah, Nurul Hidayatus; Saragih, Sahat; Prasetyo, Yanto (JIWA: Jurnal Psikologi Indonesia, 2023)
Academic stress is a condition that exists in students due to academic demands and pressures that must be done and sometimes exceed the individual's ability to deal with these demands which can cause physical and emotional distress. The purpose of this study was to determine the relationship between problem focused coping and academic stress in students. This study uses quantitative research with probability sampling technique, namely simple random sampling. The subjects in this study were active students of the Faculty of Psychology, University of August 17, 1945 Surabaya Class of 2020 involving 122 respondents. This study used a problem focused coping scale and an academic stress scale. Data analysis in this study used Spearman's Rho analysis technique IBM Staticctic Package for Social Science (SPSS) version 25 for windows. The result of this study is that there is a negative relationship between problem focused coping and academic stress in students. That is, the higher the problem focused coping, the lower the academic stress on students. Stres akademik merupakan suatu kondisi yang ada pada mahasiswa dikarenakan adanya tuntutan dan tekanan akademik yang wajib dikerjakan dan terkadang melebihi kemampuan individu dalam menghadapi tuntutan tersebut yang dapat menyebabkan tertekan baik secara fisik maupun emosional. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara problem focused coping dengan stres akademik pada mahasiswa. Penelitian ini menggunakan penelitian kuantitatif dengan teknik pengambilan sampel probability sampling yaitu simple random sampling. Subjek pada penelitian ini adalah Mahasiswa Aktif Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya Angkatan 2020 dengan melibatkan 122 responden. Penelitian ini menggunakan skala problem focused coping dan skala stres akademik. Analisis data dalam penelitian ini menggunakan teknik analisis Spearman’s Rho IBM Statisctic Package For Social Science (SPSS) versi 25 for windows. Hasil dari penelitian ini adalah terdapat hubungan negatif antara problem focused coping dengan stres akademik pada mahasiswa. Artinya, semakin tinggi problem focused coping maka semakin rendah stres akademik pada mahasiswa.